Eu(O2C‐C≡C‐CO2): An EuII Containing Anhydrous Coordination Polymer with High Stability and Negative Thermal Expansion. Issue 12 (11th February 2020) - Gramm, Verena K.; Smets, Daniel; Grzesiak, Ireneus; Block, Theresa; Pöttgen, Rainer; Suta, Markus; Wickleder, Claudia; Lorenz, Thomas; Ruschewitz, Uwe
Abstract: Anhydrous Eu II –acetylenedicarboxylate (EuADC; ADC 2− = − O2 C‐C≡C‐CO2 − ) was synthesized by reaction of EuBr2 with K2 ADC or H2 ADC in degassed water under oxygen‐free conditions. EuADC crystallizes in the SrADC type structure ( I 41 / amd, Z= 4) forming a 3D coordination polymer with a diamond‐like arrangement of Eu 2+ nodes ( msw topology including the connecting ADC 2− linkers). Deep orange coloured EuADC is stable in air and starts decomposing upon heating in an argon atmosphere only at 440 °C. Measurements of the magnetic susceptibilities ( μ eff =7.76 μB ) and 151 Eu Mössbauer spectra ( δ =−13.25 mm s −1 at 78 K) confirm the existence of Eu 2+ cations. Diffuse reflectance spectra indicate a direct optical band gap of E g =2.64 eV (470 nm), which is in accordance with the orange colour of the material. Surprisingly, EuADC does not show any photoluminescence under irradiation with UV light of different wavelengths. Similar to SrADC, EuADC exhibits a negative thermal volume expansion below room temperature with a volume expansion coefficient α V =−9.4(12)×10 −6 K −1 . Abstract : Multifaceted ! Orange coloured Eu(C4 O4 ), the anhydrous Eu II salt of acetylenedicarboxylic acid, has many interesting properties: it is stable in air for months, and upon heating in an inert atmosphere decomposition only starts at 440 °C. Below room temperature it shows a negative thermal volume expansion (NTE) and although containing Eu II it does not exhibit any luminescence even at 10 K.